Synthesis and Complexation Behaviour of 1,3-Bis(2-pyridylimino)isoindole with Nickel(II) - KASIM SENER, M. (Asian Journal of Chemistry, 2010)
The synthesis and complex behaviour of 1,3-bis(2-pyridylimino) isoindoline (2) with nickel(II) is reported. The new compounds were characterized by elemental analysis, FT-IR, 13C NMR, 1H NMR and via mass spectrometric analysis. Electrochemical properties of the [(4,5-bis(hydroxyethylmercapto)-bis(2- pyridylimino)-isoindoline)Ni(OAc)(H2O)] was also studied by cyclic voltammetry.